Surface and optical characteristics of polycrystalline GaN layer with different pores profile of porous GaAs/GaAs substrate - Md Taib, Muhamad Ikram; Samsudin, Muhammad Esmed Alif; Alias, Ezzah Azimah; Waheeda, S.N.; Ibrahim, Nurul Farhana; Shuhaimi, Ahmad; Zainal, Norzaini (IOP Publishing, 2019)
This work investigated the influence of pores profile of a porous GaAs/GaAs substrate on surface and optical characteristics of an over-deposited GaN layer. Different pores profile of the porous GaAs/GaAs substrate was introduced by varying the DMF concentration of 50%, 75% and 90%. The pores distribution is more uniform, while the pores size is bigger with higher DMF concentration. In contrast, the pores depth is less deep when the DMF concentration was higher than 75%. Next, the GaN layer was deposited onto the porous GaAs/GaAs substrate using an e-beam evaporator system, followed by thermal annealing in ammonia ambient. It was found that the porous GaAs/GaAs substrate, etched by the DMF concentration above 75% gave lower surface roughness to the polycrystalline GaN layer although the surface morphology showed no significant changes. XRD measurement showed on non-porous substrate favoured hexagonal growth in the polycrystalline GaN layer. Instead, the porous GaAs/GaAs substrate favoured the cubic growth, especially the porous GaAs/GaAs substrate etched by 75% DMF concentration. Moreover, the GaN layer on the porous GaAs/GaAs substrate etched by 75% DMF concentration showed the smallest FWHM of NBE peak emission, while exhibited a relaxation level closer to a reported stress-free bulk GaN, as compared to other samples. After all, the porous GaAs/GaAs substrate, etched by 75% DMF concentration has improved the surface and optical characteristics of the layer due to its better porosity. © 2019 IOP Publishing Ltd.